Microclimate effects and influential mechanisms of four urban tree species underneath the canopy in hot and humid areas - Feng, Xianhui; Wen, Huan; He, Mu; Xiao, Yiqiang (Frontiers in Environmental Science, 2023)
【Purpose】Urban trees play a key role in ameliorating extreme urban climates in cities. At the micro-level, it is crucial to investigate the variations in microclimate affected by the canopy of different tree species. The significance of this research is to provide scientific evidence for selection of tree species in urban planning that can improve the local microclimate. This study examines the factors of microclimate (air temperature, relative humidity, wind environment and solar radiation) underneath the canopy of four different evergreen tree species in hot and humid area. Furthermore, the correlation between the physiological characteristics of these tree species and microclimate was analyzed by statistically analysis the data of physiological parameters of the trees and microclimate factors. 【Methods】 In this study, four tree species were selected for field measurements: Ficus microcarpa L.f., Ficus virens Aiton, Bauhinia x blakeana Dunn, Cinnamomum camphora (L.) Presl. We used the HOBE (H21-0024, onset) to measure three climatic parameters (Temperature, Relative Humidity and Instantaneous Wind Speed); the Li-6400 Portable Photosynthesis System to measure five plant physiological parameters (Stomatal Conductance (Gs), Leaf Temperature (Tleaf), Leaf Surface Relative Humidity (RHsfc), Photosynthetically Active Radiation (PAR), Leaf-level Vapor Pressure Deficit (Vpdl). The observations were conducted during the winter season (January 16 - January 22), and summer season (August 7 - August 22). The investigation periods were 9:00-11:00, 12:00-14:00 and 16:00-18:00 and data was recorded at 15-minute intervals. The observational data obtained were analyzed using statistical methods, including one-way analysis of variance, Pearson correlation coefficient and multiple regression analysis. 【Results】The results of this study indicated that the four tree species being measured had different effects on the microclimate at the site in both the winter and summer seasons. During the 7-day observation in the summer, the cooling effect of the four tree species was significant. The relative humidity underneath the canopy was 3%-11% higher than that of weather stations. The instantaneous wind speed in the afternoon was relatively higher than at other times. The solar radiation intensity was dramatically reduced by 85%-95%. During the 7-day observation in the winter，the trees had a warming effect in the morning.